The predominance of Hepatitis C Virus Genotypes and Its Association with the Viral Load in Bangladeshi Population (Bioresearch Communications, 2021)
Determination of hepatitis C virus (HCV) genotype and viral load are two significant prognostic and assessment markers of treatment decisions. The study aimed to determine the predominant HCV types or subtypes and any association with the viral load in Bangladeshi chronic HCV infected patients. A total of 359 anti-HCV positive patients underwent investigation to estimate viral load and determination of genotype and subtype using real-time reverse transcriptase polymerase chain reaction (real-time RT-PCR). Among 306 detectable viral loads containing individuals, 278 (90.85%) genotyped successfully, and 28 (9.15%) had unknown genotypes. Among typable genotypes, 1a accounted for 14 (5.03%), 1b for 14 (5.03%), 3 for 247 (88.85%), 4 for 2 (0.72%) and genotype 6 for 1 (0.36%). Based on pre-treatment viral load levels, study subjects classified into three categories such as low (500000 IU/mL). The majority of HCV other types (1a, 1b, 4, 6) infected patients (96.4%) had intermediate to high viral load compared to those infected with genotype 3 (77.7%) and unclassified types (55.0%) (χ2 =15.41; p = 0.004). HCV type 3 was prevalent (68.4%) in the above 40 years of group compared to less than 40 years group (31.6%). HCV genotype 3 was the predominant genotype circulating in Bangladesh. Pre-treatment viral load demonstrated significant difference among individuals having HCV other types and type 3. However, sequencing the HCV genome analysis would determine the exact types and subtypes among all possible HCV strains available in Bangladesh.Bioresearch Commu. 7(1): 955-959, 2021 (January)